Fear and Falling in Love with the Future: Field Notes from a Time-Travelling Educator - Planck, Sebastian (Tidsskrift for Social Innovation & Transformativ Entreprenørskabsdidaktik (SITE), 2026)
Explores the lived experience of facilitating speculative design (SD) workshops in entrepreneurship and sustainability education through a dialogic structure that moves between the internal monologue of an educator navigating fear, uncertainty, and self-doubt, and scholarly explanations of SD's history, methods, and pedagogical implications.